The effectiveness of shin guards used by football players - (:unkn) unknown (My University, 2014)
In football, injuries from opponent contact occur commonly in the lower extremities. FIFA the world's governing body for football requires players to wear shin guards. The aim of this study was to compare the protective effectiveness of polypropylene based shin guards with custom-made carbon fiber ones. Three commercial polypropylene shin guards (Adidas Predator™, Adidas UCL™, and Nike Mercurial™) and two custom-made carbon fiber shin guards were examined. The experimental setup had the following parts: 1) A pendulum attached a load cell at the tip (CAS Corp., Korea) and a fixed prosthetic foot equipped with a cleat to simulate an attacker's foot. 2) An artificial tibia prepared by condensed foam and reinforced by carbon fibers protected with soft clothing. 3) A multifunctional sensor system (Tekscan Corp., F-Socket System, Turkey) to record the impact on the tibia. In the low impact force trials, only 2.79-9.63 % of the load was transmitted to the sensors. When comparing for mean force, peak force and impulse, both carbon fiber shin guards performed better than the commercial ones (Adidas Predator™, Adidas UCL™, and Nike Mercurial™) (p = 0.000). Based on these same parameters, the Nike Mercurial™ provided better protection than the Adidas Predator™ and the Adidas UCL™ (p = 0.000). In the high impact force trials, only 5.16-10.90 % of the load was transmitted to the sensors. For peak force and impulse, the carbon fiber shin guards provided better protection than all the others. Carbon fiber shin guards possess protective qualities superior to those of commercial polypropylene shin guards. Key PointsShin guards decrease the risk of serious injuries.Carbon shin guards provide sufficient protection against high impact forces.Commercially available Polypropylene based shin guards do not provide sufficient protection against high impact forces.
Keywords: prevention; carbon; Football; force; shin guard